Pendekatan Dakwah kepada Masyarakat India Muslim: Kajian ke Atas Persekutuan Muslimin Indo-Malaysia (PERMIM) - Mohd Yunus, Ahmad Redzuwan; Che Mama, Che Yusoff (Jurnal Usuluddin, 2003)
This article based on the findings of the study done by the writer to investigate the methodology of the Islamic dakwah (mission) performed by the Malaysia Muslim lndo-Malaysian Federation (PERMIM) among the Indian Muslim communities. Library research, interview and observation are among methods used to collect data for this research. The result of the study shows that there are some methods that are widely used by the federation such as education, economic, media and social interaction.